2021
DOI: 10.1111/jpm.12735
|View full text |Cite
|
Sign up to set email alerts
|

Family environment and depressive episode are associated with relapse after first‐episode psychosis

Abstract: What is known on the subject? • Relapse rates are high among patients who have experienced first-episode psychosis (FEP). How to cite this article: da Silva AHS, de Freitas LA, Shuhama R, et al. Family environment and depressive episode are associated with relapse after first-episode psychosis. J

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(106 reference statements)
0
2
1
Order By: Relevance
“…Depression scores at baseline and at the first month did not correlate to insight at baseline and the first month, contrary to what some evidence suggests [ 14 , 15 , 16 ], and nor did they predict relapse at the year as other research shows [ 17 ]. They are, however, in agreement with other evidence showing no stable link between insight and depression, hopelessness, or suicidality [ 49 , 51 ] at baseline and the first month.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Depression scores at baseline and at the first month did not correlate to insight at baseline and the first month, contrary to what some evidence suggests [ 14 , 15 , 16 ], and nor did they predict relapse at the year as other research shows [ 17 ]. They are, however, in agreement with other evidence showing no stable link between insight and depression, hopelessness, or suicidality [ 49 , 51 ] at baseline and the first month.…”
Section: Discussioncontrasting
confidence: 86%
“…Unfortunately, early insight and depression have been associated with suicide attempts and with actual suicides within four years after the first episode, which is a known major cause of mortality for schizophrenia patients [ 16 ]. In terms of relapse, recent research has shown contradictory results on whether depressive symptoms may predict relapse after FEP or not [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bird et al (2010) showed that a good family atmosphere can reduce hospitalization rates among people diagnosed with mental illness. da Silva et al (2021) showed that the family environment is a predictor of relapse among people diagnosed with mental illness and that the importance of family interventions in the treatment of mental illness should be emphasized. These studies suggested that healthcare professionals should pay attention to the home environment of patients diagnosed with anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%